2017
DOI: 10.3390/su9091569
|View full text |Cite
|
Sign up to set email alerts
|

Status of Underutilised Crops in South Africa: Opportunities for Developing Research Capacity

Abstract: Underutilised crops represent an important component of agro-biodiversity with potential to contribute to climate change adaptation, food security and sovereignty in poor rural areas. However, despite emerging research interest, they continue to occupy the peripheries of mainstream agriculture. There is a need to consolidate the gains made and propose a coherent strategy for translating underutilised crops into mainstream agriculture. The status of underutilised crops in South Africa (past, present and on-goin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
111
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 48 publications
3
111
0
1
Order By: Relevance
“…The current study is a sequel to an initial study on the status of NUS in South Africa, which recommended prioritizing NUS and developing a strategy to promote them (Mabhaudhi et al, 2017). The current study was structured into two stages, (i) identifying priority drought tolerant and nutrient dense NUS, and (ii) outlining a roadmap for promoting research, development and innovation for the identified NUS in South Africa.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The current study is a sequel to an initial study on the status of NUS in South Africa, which recommended prioritizing NUS and developing a strategy to promote them (Mabhaudhi et al, 2017). The current study was structured into two stages, (i) identifying priority drought tolerant and nutrient dense NUS, and (ii) outlining a roadmap for promoting research, development and innovation for the identified NUS in South Africa.…”
Section: Methodsmentioning
confidence: 99%
“…The five (5) commonly used terms that were identified were; (i) underutilized crops, (ii) indigenous crops, (iii) traditional crops, (iv) neglected crops, and (v) orphan crops. This was based on common terminology identified in the initial study (Mabhaudhi et al, 2017). The terms were used to conduct online searches using Google® and Google Scholar®, Scopus, ScienceDirect and SpringerLink search engines.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations